Performance of Low-temperature Two-stage Transcritical CO2 Compression Refrigeration System with Ejector - Fu Bing; Zhang Liang; Ye Fangping; Jiao Xingrong; Yang Yuqi (Zhileng xuebao)
Because of the limited experimental studies on transcritical CO2 refrigeration systems at low evaporating temperatures, an experimental platform of a two-stage transcritical CO2 compression refrigeration system with an ejector was designed and built. We evaluated the performance of the proposed refrigeration system under the following experimental conditions: evaporating temperature within the range of -33 ℃--29 ℃, gas cooler outlet temperature of 30 ℃-40 ℃, and high pressure of 8.20 MPa-9.70 MPa. The results show that the variation trend of the experimental results is consistent with that of the theoretical thermodynamic calculation results, and the application of the ejector can significantly improve the performance of the two-stage transcritical CO2 compression refrigeration system. The maximum increase rate of the coefficient of performance (COP) of the refrigeration system by the ejector is 29.37%. Under experimental conditions, the optimal high pressure of the two-stage transcritical CO2 compression refrigeration system with an ejector is 8.80 MPa, and the corresponding optimal COP is 1.63. The cooling capacity and COP of the two-stage transcritical CO2 compression refrigeration system with an ejector increase with increasing evaporating temperature, and the gas cooler outlet temperature significantly affected the performance of the refrigeration system. As the gas cooler outlet temperature increases from 30 ℃ to 40 ℃, the COP of the refrigeration system decreases by 61.4%. The research results provide a reference for research on two-stage transcritical CO2 compression refrigeration systems with ejectors.